Caring for the dead? An alternative perspective on Sámi reburial - Svestad, Asgeir (Acta Borealia, 2019)
This is an Accepted Manuscript of an article published by Taylor & Francis in Acta Borealia on 29 Apr 2019, available online: http://www.tandfonline.com/ https://doi.org/10.1080/08003831.2019.1607065 . This article is an effort to critically discuss Sámi repatriation and reburial practice based on the analysis of five repatriation cases. Since the seminal repatriation (and burial) of the skulls of Somby and Hætta in Gávvuonna/Kåfjord in 1997, and the more recent reburial of 94 skeletons in Njauddâm/Neiden in 2011, a precedent seems established in Norway that allows the unconditional reburial of all Sámi human remains from collections and excavations. This inevitably poses a serious challenge to research on Sámi human remains and the Sámi past. It is argued that what is important is not research, but that Sámi are allowed to decide for themselves how they wish to care for the dead. Rather than argue according to the adversarial pro-research or pro-reburial viewpoints, this article will take a closer look at how the dead, and their associated material remains, are cared for during Sámi reburial. As will be argued, the care for the material side tends to be neglected and therefore raises an ethical question regarding this practice.